BECOMING ENGLISH TEACHERS IN ENGLISH AS AN INTERNATIONAL LANGUAGE (EIL) CONTEXT IN INDONESIA - Supartini (2013)
The paper entitled 'Becoming English Teachers in English as an International Language (EIL) Context in Indonesia', discusses the construction of English teachers' identity in English as an International Language (EIL) context in Indonesia. Utilizing narrative inquiry and case study as research method, personal teaching and learning experiences of two English teachers of a private university in Purwokerto, Central Java are gathered through semi-structured interviews presented through retelling technique. From the research findings, it is revealed that the teachers' identity is constructed through three ways; positioning, being positioned, and negotiating. In addition, it is also suggested that English Language Teaching (ELT) in English as an International Language (EIL) context should emphasize more pedagogical competence and language mastery rather than native speakerism.